DETERMINAN KELELAHAN KERJA PADA KARYAWAN GEN Z PT. ADHI PERSADA GEDUNG KANTOR CABANG SURABAYA - Dimas Dwiky Putranto; Ana Kadarningsih; Tito Wira Eka Suryawijaya (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
This research aims to determine the influence of work motivation, working hours and work environment on work fatigue in Gen Z employees, which is then compared with fatigue in employees other than Gen Z. This research uses quantitative methods and collects data by distributing questionnaires online. The research population is employees of PT. Adhi Persada Building. The sample was selected using purposive sampling with stratified sampling theory. The data was analyzed using linear regression analysis for Gen Z employees. The results showed that the variables of work motivation and working hours obtained significant values for Gen Z work fatigue. Work environment variables could not influence the work fatigue of Gen Z employees. So, with good work motivation and working hours work in accordance with the provisions, a company can reduce the level of employee work fatigue, by evaluating the factors that can influence employee work fatigue.